Development and validation of risk-stratified biopsy decision pathways incorporating MRI and PSA-derived indicators - Pengfei Jin; Ximing Wang; Zhenwei Ding; Liqin Yang; Chenyang Xu; Xu Wang; Fawei Huang (Annals of Medicine)
Objectives Develop risk-adapted conditional biopsy pathways utilizing MRI in combination with prostate-specific antigen (PSA) density (PSAD) and the ratio of free to total PSA (f/tPSA), respectively, to enhance the detection of clinically significant prostate cancer (csPCa) while minimizing ‘negative’ biopsies in low-risk patients.Methods The Prostate Imaging Reporting and Data System (PI-RADS) category, PSAD, f/tPSA and biopsy-pathology of 1018 patients were collected retrospectively. Subsequently, PSAD and f/tPSA were divided into four intervals, which were then combined with the MRI findings to construct two risk stratification matrix tables. Six biopsy decision pathways were established: three clinical pathways based solely on PSAD and f/tPSA, and three MRI-combined pathways incorporating both PI-RADS and PSA-derived indicators. The biopsy and clinically insignificant PCa (ciPCa) avoidance, csPCa detection rate, and ‘negative’ biopsies proportion were assessed. Decision curve analysis (DCA) was employed to evaluate the net benefit associated with each pathway.Results When reporting PI-RADS 1 - 2, PSAD ≥ 0.20 ng/ml/cm3 or f/tPSA ≤ 0.10 were found to be useful for patient stratification. When reporting PI-RADS 3, PSAD ≥ 0.10 − 0.15 ng/ml/cm3 and f/tPSA ≤ 0.16 − 0.25 were helpful in distinguishing the risk of csPCa. The three MRI-combined pathways showed higher csPCa detection rates (94% to 96%) than the three clinical pathways (85% to 91%); ‘MRI + PSAD + f/tPSA’ demonstrated a high csPCa detection rate of 94% while maintaining the maximum biopsy avoidance and lowest ‘negative’ biopsy proportion of 40% and 25%, respectively. The DCA showed significantly higher net benefits for three MRI-combined pathways compared to all clinical pathways.Conclusions The integration of MRI and PSA-derived indicators enables effective patient risk stratification, thereby providing valuable decision-making pathways to enhance the management of csPCa while minimizing ‘negative’ biopsies.